KONFLIK KEPENTINGAN DALAM PENGELOLAAN TANAH ADAT DI DESA BEBIDAS KABUPATEN LOMBOK TIMUR - Hasnika Hasnika; Nurun Sholeh; Robyan Endru Bafadal (Universitas Hamzanwadi, 2020)
This study aims to determine conflicts and the impact of conflicts of interest on customary land management patterns in Bebidas Village, East Lombok. This research is a descriptive study in which data is collected in words, pictures, and not numbers. The results showed that the management of the Jurang Koak customary land was carried out collectively by the people of Jurang Koak daily land and had been managed by their ancestors since the Dutch East Indies era. However, since 1997, Mount Rinjani National Park has been designated as a wildlife reserve by the Minister of Forestry. Since then, in the Jurang Koak customary land, there has been a conflict between the Jurang Koak indigenous people and the Mount Rinjani National Park in the management of customary land. The community wants to use the land as agricultural land, but the National Park wants customary land as a conservation forest for Mount Rinjani National Park.